Evaluation of psychological status in early-stage breast cancer outpatients: a cross-sectional study utilizing the Kessler 10 Scale - Zhaoju Zhou; Jing Yuan; Ying Zhang; Ping Wu; Wenjie Lv (BMC Psychiatry)
Abstract Objective To evaluate the psychological status of early-stage breast cancer outpatients using the Kessler 10 Scale (K10) and to determine the feasibility of employing the K10 scale for psychological assessment in outpatient settings. Methods This cross-sectional study surveyed 250 patients at the Breast Surgery Outpatient Clinic of our hospital, from February to March 2023, using the Kessler 10 Scale (K10) questionnaire. Results A total of 120 breast cancer (BC) patients and 120 non-breast cancer (non-BC) patients completed the questionnaire. The K10 scores were significantly higher in BC patients compared to non-BC patients (15 [12.25, 20] vs. 13.5 [11.25, 17], P = 0.006). Among BC patients, those receiving postoperative endocrine therapy had significantly higher K10 scores than those not (19 [14, 22] vs. 15 [12, 20], P = 0.04). However, the type of surgery did not significantly impact the psychological status of BC patients (P = 0.57). Conclusions The Kessler 10 Scale (K10) is a practical tool for initial psychological screening in outpatient settings. BC patients demonstrate significantly higher levels of psychological distress compared to non-BC patients. Patients undergoing endocrine therapy as part of adjuvant treatment following surgery experience greater psychological distress compared to those not. These findings underscore the importance of early psychological monitoring and intervention for this population during outpatient visits.